Triangle of sadness [videorecording (DVD)] - Östlund, Ruben, 1974-; Dickinson, Harris, 1996-; Dean, Charlbi, 1990-2022; De Leon, Dolly, 1969-; Buric, Zlatko, 1953-; Berben, Iris, 1950-; Berlin, Vicki, 1977-; Dorsin, Henrik, 1977-; Folly, Jean-Christophe; Walker, Amanda; Davies, Oliver Ford; Melles von Rohonczy, Sunnyi; et al. (Criterion collection, 2023)
"A model-influencer couple get a ticket to the luxe life when they are invited aboard an all-expenses-paid cruise alongside a coterie of the rich and ghoulish, but an act of fate turns their Insta-perfect world upside down" --